Comparison of Automated Activity Recognition to Provider Observations of Patient Mobility in the ICU*. Issue 9 (September 2019) - Rawat, Nishi; Rao, Vishal; Peven, Michael; Shrock, Christine; Reiter, Austin; Saria, Suchi; Ali, Haider
Abstract : Objectives: To compare noninvasive mobility sensor patient motion signature to direct observations by physicians and nurses. Design: Prospective, observational study. Setting: Academic hospital surgical ICU. Patients and Measurements: A total of 2, 426 1-minute clips from six ICU patients (development dataset) and 4, 824 1-minute clips from five patients (test dataset). Interventions: None. Main Results: Noninvasive mobility sensor achieved a minute-level accuracy of 94.2% (2, 138/2, 272) and an hour-level accuracy of 81.4% (70/86). Conclusions: The automated noninvasive mobility sensor system represents a significant departure from current manual measurement and reporting used in clinical care, lowering the burden of measurement and documentation on caregivers. Abstract : Supplemental Digital Content is available in the text.